2022
DOI: 10.1007/s11154-022-09754-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health care provider knowledge of diabetes and diabetic microvascular complications: a comprehensive literature review

Abstract: Diabetic retinopathy, neuropathy, and nephropathy occur in more than 50% of people with diabetes, contributing substantially to morbidity and mortality. Patient understanding of these microvascular complications is essential to ensure early recognition and treatment of these sequalae as well as associated symptoms, yet little is known about patient knowledge of microvascular sequalae. In this comprehensive literature review, we provide an overview of existing knowledge regarding patient knowledge of diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 149 publications
0
10
0
3
Order By: Relevance
“…More than 50 % of DM patients present with retinopathy, nephropathy and nervous system lesions, with high morbidity and mortality. [121] DM has caused serious economic burden to the whole society. How to prevent and treat the occurrence and development of DM and related complications is an urgent public health problem.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50 % of DM patients present with retinopathy, nephropathy and nervous system lesions, with high morbidity and mortality. [121] DM has caused serious economic burden to the whole society. How to prevent and treat the occurrence and development of DM and related complications is an urgent public health problem.…”
Section: Diabetesmentioning
confidence: 99%
“…DM can also damage multiple tissues and organs. More than 50 % of DM patients present with retinopathy, nephropathy and nervous system lesions, with high morbidity and mortality [121] . DM has caused serious economic burden to the whole society.…”
Section: Research Progress Of Prebiotic Inulin In Diseasesmentioning
confidence: 99%
“…Poorly managed diabetes can cause a variety of headaches ranging from microvascular to macrovascular, including coronary artery disease, renal failure, blindness, stroke, skin ulcers, particularly within the foot, and so on, all of which can result in significant morbidity and mortality [11]. Diabetes is the most serious hazard to the progression and development of DM complications.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“… 16 Healthcare professionals with a thorough understanding of disease management and practical experience are essential for delivering high-quality healthcare services and treatments. 17 , 18 However, in the context of DKD, limited research exists on KAP among nephrologists. A qualitative study found only 56% of healthcare workers perform kidney function assessments in Type 2 Diabetes patients, and merely 25% use urinary albumin for DKD monitoring and staging.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature review further underscores the limited attention given to DKD-related KAP among healthcare workers and emphasizes the imperative for additional research in this domain. 18 Consequently, the research questions are: 1) What are the current levels of KAP among healthcare workers regarding DKD management? and 2) What factors influence these dimensions?…”
Section: Introductionmentioning
confidence: 99%